Statistics and Probability for Engineering Applications. - DeCoursey, William
Makes statistical methods easier and accessible to engineers. This book points the reader to the topics and sections pertinent to a particular type of statistical problem. It includes a CD-ROM that contains the Excel data sets for the examples and case studies given in the book, along with other statistical tools and software.